Impact of Sea Surface Temperature Variability at Different Ocean Basins on Dust Activities in the Gobi Desert and North China - Guanyu Liu; Jing Li; Zhongjing Jiang; Xichen Li (Geophysical Research Letters)
Abstract Dust activities are closely related to local meteorological conditions partly driven by remote ocean variability. Here, we investigate the impact of tropical Pacific, North Atlantic, and Arctic ocean variability on dust activities in the Gobi Desert and North China and attempt to quantify their contributions. Three individual Sea Surface Temperature (SST) forcing experiments were performed to simulate the teleconnection from the three ocean basins. Two random forest regression models were established to link the meteorological variables to boreal Spring Dust Activity Frequency (SDAF). Results show that with SST (sea ice concentration for the Arctic) anomaly, tropical Pacific SST variability results in the most change in SDAF in the Gobi Desert, whereas the North Atlantic SST variability plays a more critical role in North China. Considering the observed SST variability, the tropical Pacific becomes more critical in affecting dust activities in both regions.